Revitalizing Minangkabau Traditional Values as a Solution to the Multicultural Education Crisis in West Sumatra - Gucandra, Yudi; Aprison, Wedra (Fakultas Agama Islam Universitas Muhammadiyah Sumatera Barat, 2025)
This study analyzes the paradox of multicultural education in West Sumatra, where the Minangkabau traditional philosophy, rich in egalitarian and tolerant values, has not been optimally integrated into the formal education system, triggering a crisis marked by religious intolerance, bullying, and ethnic tensions. Using a qualitative approach with hermeneutic methods and content analysis of policy documents, media reports (2024-2025), and academic literature, this study identifies systemic failures in Banks' five dimensions of multicultural education: Prejudice Reduction (religious intolerance), Equity Pedagogy and Empowering School Culture (bullying), and Content Integration and Knowledge Construction (ethnic tension). The findings show that the crisis is not caused by the absence of tolerance values, but rather by the failure to translate traditional philosophy into concrete practice. This study proposes a model for revitalizing Minangkabau traditional values as a contextual solution: (1) ABS-SBK interpreted inclusively to reduce prejudice; (2) deliberative consensus as the basis for equitable pedagogy; (3) the principles of